DNA methylation and single nucleotide variants in the brain-derived neurotrophic factor (BDNF) and oxytocin receptor (OXTR) genes are associated with anxiety/depression in older women - Chagnon, Yvon C.; Potvin, Olivier; Hudon, Carol; Préville, Michel (Frontiers in Genetics, 2015)
Background: Environmental effects and personal experiences could be expressed in individuals through epigenetic non-structural changes such as DNA methylation. This methylation could up- regulate or down-regulate corresponding gene expressions and modify related phenotypes. DNA methylation increases with ageing and could be related to the late expression of some forms of mental disease. The objective of this study was to evaluate the association between anxiety disorders and/or depression in older women and DNA methylation for four genes related to anxiety or depression. Methods: Women aged 65 and older with (n =19) or without (n =24) anxiety disorders and/or major depressive episode (DSM-IV), were recruited. DNA methylation and single nucleotide variant (SNV) were evaluated from saliva, respectively by pyrosequencing and by PCR, for the following genes: brain-derived neurotrophic factor (BDNF; rs6265), oxytocin receptor (OXTR; rs53576), serotonin transporter (SLC6A4; rs25531) and apolipoprotein E (APOE; rs429358 and rs7412). Results: A greater BDNF DNA methylation was observed in subjects with anxiety/depression compared to control group subjects(Mean: 2.92 SD: 0.74 vs. 2.34 SD: 0.42; p=0.0026).This difference was more pronounced in subjects carrying the BDNF rs6265 CT genotype (2.99 SD: 0.41 vs.2.27 SD: 0.26; p=0.0006) than those carrying the CC genotype (p=0.0332); no subjects with the TT genotype were observed. For OXTR, a greater DNA methylation was observed in subjects with anxiety/depression, but only for those carrying the AA genotype of the OXTR rs53576SNV, more particularly at one out of the seven CpGs studied (7.01 SD: 0.94 vs. 4.44 SD: 1.11; p=0.0063). No significant differences were observed for APOE and SLC6A4. Conclusion: These results suggest that DNA methylation in interaction with SNV variations in BDNF and OXTR, are associated with the occurrence of anxiety/depression in older women.